ANALISIS PORTOFOLIO OPTIMAL INVESTASI DANA PENSIUN DI INDONESIA - Tutut Luckyta Rosananda; Syamsul Hadi (Program Studi Ekonomi Pembangunan, 2018)
This study aims to analyze the optimal portfolio investment of Pension Fund in Indonesia that provide optimal returns at certain risk levels in 2005-2016. Data collection in this study used secondary data obtained from the Financial Services Authority (OJK). Investment instruments under study are Government Bond (SBN), Deposit and Saving, Share, Bond and Islamic Bond, Mutual Funds, Land and Building. Data analysis technique used is using Markowitz method with optimal portfolio selection based on investor preference. The results of this study indicate that: First, the optimal portfolio based on investor preferences who like the risk is obtained that the largest proportion is in the share investment instruments of 153.41%. Secondly, an optimal portfolio based on investor preference that is neutral to risk is obtained that the largest proportion is in share investment instrument of 84.28%. Third, an optimal portfolio based on investor preferences that does not like risk is found that the largest proportion is found in investment instrument land and building of 39.30%.Keywords: Pension Fund, Portfolio, Investment, Markowitz.